Comparison of Efficacy and Safety of Single and Double Immune Checkpoint Inhibitor-Based First-Line Treatments for Advanced Driver-Gene Wild-Type Non-Small Cell Lung Cancer: A Systematic Review and Network Meta-Analysis - Xu, Qian; Zhang, Xue; Huang, Miao; Dai, Xin; Gao, Jing; Li, Song; Sheng, Lei; Huang, Kai; Wang, Jian; Liu, Lian (Frontiers in Immunology, 2021)
Background: Immune checkpoint inhibitors (ICIs) have improved survival for advanced wild-type NSCLC significantly, but few studies compared single ICI (SICI)-based treatments and double ICIs (DICI)-based treatments. We summarized the general efficacy of ICIs-related treatments, compared the efficacy and safety of SICI-based (PD-1/L1 or CTLA-4 inhibitors±chemotherapy) and DICI-based (PD-1/L1 inhibitors+CTLA-4 inhibitors±chemotherapy) treatments versus CT in the first-line treatment. Methods: We included phase II/III randomized controlled trials (RCTs), including patients of histologically confirmed stage IIIB-IV driver-gene wild-type NSCLC who received first-line ICI-related therapy in at least one arm. PubMed, Embase, and Cochrane library were searched from Jan 1, 2005 to Dec 31, 2020. This network meta-analysis was performed in a Bayesian framework using GEMTC and JAGS package in R.3.6.1. The research was registered with PROSPERO (CRD42020184534). Results: 20 RCTs were involved, including 13032 patients and 17 treatment regimens. The results showed ICI-based therapies could provide a pooled mOS (POS) of 15.79 (95% CI: 14.85-16.73) months and there were no significant differences in overall survival (OS), progression-free survival (PFS), overall response rate (ORR), and ≥3 adverse events (≥3AEs) between DICI-based treatments (POS: 14.81, 12.11-17.52months) and SICI-based treatments (POS: 16.17, 14.59-17.74 months) in overall patients. However, DICI-based treatments had significantly prolonged the OS over SICI-based treatments in squamous and PD-L1<1% subgroups. The ranking of OS benefit by Bayesian SUCRA spectrum showed that DICI+chemotherapy ranked first for overall population and subgroups including squamous, non-squamous, any level of PD-L1 expression, smoking, male, ECOG PS=0/1, age<65/≥65, while SICI+CT for low tumor mutation burden (TMB), non-smoking, and female subgroups, and DICI for high TMB subgroups. Conclusions: In the first-line therapy for advanced wild-type NSCLC, both SICI- and DICI-based treatments could bring significant overall advantages over chemotherapy, with comparable outcomes of efficacy and ≥3AEs. DICI-based treatments were more effective than SICI-based treatments in squamous and PD-L1<1% subgroups. For most populations, DICI+chemotherapy could be the best choice with a survival benefit, while SICI+chemotherapy has established its position actually.